2023
DOI: 10.3390/polym15153188
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the Water Pollutant Ciprofloxacin Using Biodegradable Sorbent Polymers Obtained from Polysaccharides

Abstract: Water use has been increasing globally by 1% per year, and recycling and re-use are critical issues compromised by the presence of pollutants. In this context, the design of novel materials and/or procedures for the large scale-removal of pollutants must be economically and environmentally feasible in order to be considered as part of the solution by emerging economies. We demonstrate that the cross-linking of biodegradable polysaccharides such as starch, dextrin, or dextrin and β-cyclodextrin with divinyl sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The search for sorbent materials is driven not only by their affinity for pollutants but also by the sustainability of their production. We previously reported that it is feasible to obtain sorbent polymers by cross-linking biodegradable carbohydrates with DVS and the ecofriendly material resulting from the cross-linking of starch shows a high affinity for CIP, making it suitable for inland water and seawater remediation [ 14 , 15 , 16 ]. Nevertheless, this approach failed to yield sorbent materials capable of capturing IBU despite both CIP and IBU showing a certain degree of structural similarity ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The search for sorbent materials is driven not only by their affinity for pollutants but also by the sustainability of their production. We previously reported that it is feasible to obtain sorbent polymers by cross-linking biodegradable carbohydrates with DVS and the ecofriendly material resulting from the cross-linking of starch shows a high affinity for CIP, making it suitable for inland water and seawater remediation [ 14 , 15 , 16 ]. Nevertheless, this approach failed to yield sorbent materials capable of capturing IBU despite both CIP and IBU showing a certain degree of structural similarity ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Natural polymers such as chitosan, cyclodextrin, sodium alginate, starch, cellulose, lignin, and their derivatives have been used to prepare molecular imprinted polymers (MIPs) [ 20 ]. In addition, along with our previous research, we have generated a library of polymers using starch, Dx, and/or β-cyclodextrin as building blocks [ 14 , 15 , 16 ]. However, for the purposes of this work, we have focused on Dx because, unlike starch, it exhibits excellent water solubility and, as a linear molecule, it is more flexible than cyclodextrins because the cavities are not preformed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations